Myoepithelial Carcinoma arising in a background of pleomorphic adenoma - Yaqoob, Nausheen; Mansoor, Salima; Aftab, Kanwal; Memon, Riyasat Ahmed; Jamal, Saba (Journal of the Pakistan Medical Association, 2022)
Carcinoma ex pleomorphic adenoma is a neoplasm of the salivary gland that causes 3.6% of salivary gland tumours and 12% of salivary gland malignancies. It is a myoepithelial or epithelial neoplasm that arises from pleomorphic adenoma, whether primary or recurrent. Historically carcinoma ex pleomorphic adenoma is considered a high-grade malignancy. Salivary duct carcinoma and high-grade adenocarcinoma are the histologic types that most commonly arise in the background of Pleomorphic adenoma. However, 15% of tumours arising in Pleomorphic adenoma are considered low grade and have sluggish growth. Low-grade carcinoma ex pleomorphic adenoma can be difficult to differentiate from cellular pleomorphic adenoma. The case of a 56-year-old female patient who had neck swelling is being presented. The biopsy showed spindle cell component with mild atypia, invasion into surrounding tissue, and increased mitotic activity on the basis ---Continue